Mihail Sebastian și poetica romanului proustian - Paul Dugneanu (Revista de Istorie și Teorie Literară)
Playwright and modernist novelist, Mihail Sebastian was also an outstanding literary critic, proving, in the same time, remarkable theoretical skills. Concerned with the analysis of the literary phenomena from that period, he even set on putting together an extensive study in two volumes, having as subject the modernist novel. Despite the fact that he did not accomplish his project, a large part of his critical opinions and of his theoretical reflections-mostly involving the narrative constructions from ”In search of lost time“ —, can constitute an important Romanian contribution to a poetics of the proustian novel.